Report of the Committee on Enforced Disappearances - United Nations (United Nations, 2019)
This is the annual report submitted to the General Assembly by the Committee on Enforced Disappearances covering its fifteenth (5-16 November 2018) and sixteenth (8-18 April 2019) sessions.